Net operating loss policies in Poland: A tool for tax neutrality and a firm's antifragility - Christophe Cathala (Financial Internet Quarterly, 2022)
The purpose of the article is to check the impact of Net Operating Loss Policies (NOL) for firms. Net Operating Loss Policies (NOL) are a central fiscal tool because they enable firms to be taxed on their average profitability over time. A complete NOL policy has 4 dimensions: a NOL carryforward (1), carry-back (2), unlimited in time (3) and with the time value of money (4) taken into account. No country applies a complete NOL policy. To evaluate the impact of all dimensions of NOL policies, Polish firm data from 41 sectors from the BACH database over ten years, from 2011 to 2020, are analysed. The results show that the change observed in the effective tax rate is positive with a complete NOL policy. In such case, firms pay less CIT in total, showing that the state will earn less, but should get more stability from firms which will hoard more cash. More investments or firms with more equity could be reached, strengthening the state's stability. The variance confirms such intuition, an earlier use of a full or almost full fiscal deficit logically means a higher effective tax rate in years to come (but less in gross terms).
Keywords: M48; 330; corporate taxation; loss-offset; Net Operating Losses; tax neutrality; antifragility